Analisis Perubahan Penggunaan Lahan dan Arahan Pemanfaatan Ruang untuk Pertanian di Kabupaten Penajam Paser Utara, Provinsi Kalimantan Timur - Benadikta Widjayatnika; Dwi Putro Tejo Baskoro; Andrea Emma Pravitasari (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2017)
Penajam Paser Utara was one of the youngest regency in East Kalimantan which focused to develop agriculture sector, especially food crops. Contribution agriculture sector to Gross Regional Domestic Product (PDRB) in 2015 was in second position accounted for 20.97%. This research was aimed to compile direction for agricultural land use based on actual land use, regional development index and land suitability. Land use change was obtained by overlay method within two land use map (2010 and 2016) from BPN, regional development was analyzed by skalogram method using PODES data (2011 and 2014) from BPS and land suitability was evaluated referred to FAO framework using matching method between land unit mapping based on soil map 1:50,000 from BBSDLP and criteria for specific commodities. Actual land use in Penajam Paser Utara (2016) consist of forest (32.92%), plantation (25.51%), industrial forest (17.09%), bush (8.76%) and other land use (15.72%). Land use change pattern from 2010 to 2016 showed increasing of plantation area (3.55%) due to forest land decreasing (1.42%). Regional development indicated by increasing of average IPD from 21.72 (2011) to 32.04 (2014). Land suitability for agriculture was classified in S3 (marginally suitable)-N2 (permanently not suitable). Retention factors were erosion hazard (e), rooting media (r), nutrion retention (n) and nutrient availability (n). Available land for agriculture using largely 162,493 Ha consist of (a) plantation area largely 113,796 Ha (b) wetland crop largely 24,258 (c) dry land crop largely 15,101 Ha and (d) not suitable for agriculture largely 6,027 Ha.